(untitled) (Bangladesh Journal of Urology, 2020)
Controlled clinical trials are unusual in surgery, rare in urology, and almost non existent as far as the management of urethral stricture is concerned. What data there are come largely from so called “expert opinion” and the quality of this is variable. None the less, the number of so called experts, past and present, is comparatively small and in broad principle their views more or less coincide. Although this review is therefore inevitably biased, it is unlikely that expert opinion will take issue with most of the general points raised here. Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.158-163